A fluid-pressure feedback model of dehydration reactions: experiments, modelling, and application to subduction zones - Miller, Stephen Andrew; van der Zee, Wouter; Olgaard, David L.; Connolly, James A. D. (My University, 2003)
Dehydration and melting reactions generate large volumes of fluid in the crust and upper mantle, and play an important role in subduction zone seismicity. The fluid pathway must evolve from isolated pockets in low porosity, low permeability rock, coalescing to interconnected permeable pathways to the surface. When fluid pressures generated from a dehydration or melting reaction are sufficient to induce hydrofracture, then hydrofracture significantly influences the porosity-permeability structure within the dehydrating/melting horizon. If a low fluid-pressure boundary is introduced to the dehydrating rock, then fluid will be driven from the rock along the evolved permeable network toward that boundary. The resulting pressure reduction can then accelerate the dehydration reaction and further drive the flow. The sudden introduction of a low fluid-pressure boundary may occur by the co-seismic (dilatant) rupturing of a pressure seal that connects different fluid pressure states. This mechanism is invoked to explain the observed post-seismic evolution of wave velocities (V-p/V-s,) following the 1995 Antofagasta, Chile earthquake. We show experimental results and introduce a conceptual and numerical model that reflects this scenario. The model couples the mechanical and thermodynamic effects of fluid pressure with devolitization kinetics, and is quantitatively consistent with experimental studies of the dehydration of gypsum and serpentine. The experimental results show that dehydration is controlled by access to a free (drained) boundary. The model provides a mechanistic explanation for the experimental observations and has applications in understanding the role of transient transport networks on the large-scale behavior of dehydrating and melting systems. (C) 2003 Elsevier B.V. All rights reserved.